Deriving domain specific requirement pattern for Collaborative Meeting and Appointment Scheduler Domain (CMASD) - Suhaizad, Farah Nur Atiqah; Burhanudin, Raida Rasyiqa; Nordin, Azlin (The Institute of Electrical and Electronics Engineers, Inc., 2016)
Requirement engineering (RE) helps to effectively define users’ needs and produce quality set of requirements. Nonetheless, RE efforts consume a lot of resources due to many contributing and challenging factors. Requirement reuse using pattern can help to reduce the RE resources. This work investigates requirements reuse using pattern by applying and implementing the requirements patterns into domain specific application. In addition, we also created new requirement pattern for domain specific requirements for future reuse. We demonstrate the use of requirement pattern at both stages: with reuse and for reuse. Finally, a prototype was developed as a proof-of-concept that the created patterns are useful to guide the requirements engineers to produce better and quality requirements specifications.